2017
DOI: 10.1002/slct.201701235
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of One‐Dimensional‐Based Lotus‐Like Silicone/ϒ–Al2O3 Nanocomposites for Marine Fouling Release Coatings

Abstract: Prohibition on the utilization of organotins compounds in antifouling (AF), and Fouling release (FR) paints have attracted considerable ineptest as an environmentally friendly alternative. In this work, an ecofriendly series of lotus‐like nano‐structured organic‐inorganic surfaces based on vinyl terminated polydimethylsiloxane (PDMS)/ϒ‐Al2O3 nanorods composites were successfully modeled for the first time via in‐situ technique. The tailored nanocomposites were cured via hydrosilation mechanism and applied for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Further increasing in nanofiller concentration 0.7% and 1% results in the decrement in CA, i.e., 143° ± 2° and 122° ± 2°, respectively. [ 18 ] Author anchored the surface of alumina nanorod by using the treatment of graphene oxide and prepares the hybrid GO‐γ‐Al 2 O 3 nanorod (average diameter 30–40 nm). Up to the 1 wt% of nanofiller gives the good dispersion in polydimethylsiloxane (PDMS) matrix and maximum contact angle 151° with decrease in surface free energy up to 13.25.…”
Section: Introductionmentioning
confidence: 99%
“…Further increasing in nanofiller concentration 0.7% and 1% results in the decrement in CA, i.e., 143° ± 2° and 122° ± 2°, respectively. [ 18 ] Author anchored the surface of alumina nanorod by using the treatment of graphene oxide and prepares the hybrid GO‐γ‐Al 2 O 3 nanorod (average diameter 30–40 nm). Up to the 1 wt% of nanofiller gives the good dispersion in polydimethylsiloxane (PDMS) matrix and maximum contact angle 151° with decrease in surface free energy up to 13.25.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the concept of using super­hydro­phobicity to prevent bacterial growth is a direction for designing antibacterial surfaces. , Superhydrophobicity can reduce the adhesion of bacteria to the solid surface, allowing bacteria to be easily removed before a biofilm forms on the surface . Many researchers have shown that super­hydro­phobic surfaces display excellent antibacterial adhesion properties. El-Safty et al prepared a series of super­hydro­phobic surface coatings for marine antifouling. Zhang et al prepared a super­hydro­phobic surface containing a bimetallic composition (Cu/Ag) that exhibited certain antibacterial activity using a galvanic replacement approach followed by a thermal oxidation process …”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces can be produced via two strategies: (1) designing ultra-smooth surfaces; and (2) modifying rough surfaces, both based on low-surface-energy materials. [2,3,[3][4][5]5,6] Superhydrophilic surfaces can be referred to those textured and/or structured materials having a surface roughness factor (as defined in the Wenzel equation) greater than one, r > 1, on which water spreads completely and then form water across layer i. e. water would lie on such a surface as a flat film rather than in form of droplets, and hence the dirt, dust and other staining materials on the surface can be readily washed away with this super-spreading water layer. [7] The wettability of such surface is dependent on its surface free energy and surface geometrical structure.…”
Section: Introductionmentioning
confidence: 99%